Analysis of Problems in Arabic Vocabulary Learning - Muh Ridwan; Abdul Qahar Zainal; Wahyudin Hafid; Ruslan Ruslan; Bishri Abdul Karim (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to analyze the various problems arising in teaching Arabic vocabulary to Grade 8 students at MTsN 2 Makassar. It focuses on three main aspects: the forms of difficulty students experience in mastering vocabulary, the teaching methods used in vocabulary instruction, and the factors that support or hinder teaching effectiveness. This research employs a descriptive qualitative design involving 32 students, with 6 selected as interview participants. Data were collected through observation, interviews, and documentation, and analyzed inductively to obtain a factual description of classroom learning conditions. The findings reveal several major problems, including students’ limited understanding of word meanings, inaccurate pronunciation, and difficulty using vocabulary in grammatically correct sentences. Although the teacher implements communicative activities, audiovisual media, language games, and repetitive drills, their effectiveness remains limited due to differences in students’ basic language competence, low concentration, and large class sizes that limit individual attention. The study concludes that improving Arabic vocabulary instruction requires diversified strategies, expanded opportunities for practical application, and improved classroom management to promote active vocabulary use in appropriate communicative contexts.